Bioremediation Management Reduces Mass Discharge at a Chlorinated DNAPL Site. Issue 2 (12th April 2017) - Baldwin, Brett R.; Taggart, Dora; Chai, Yunzhou; Wandor, David; Biernacki, Anita; L. Sublette, Kerry; T. Wilson, John; Walecka‐Hutchison, Claudia; Coladonato, Camillo; Goodwin, Bryan
Abstract: Adaptive site management and aggressive bioremediation in the source zone of a complex chlorinated dense nonaqueous phase liquid (DNAPL) site reduced total chlorinated hydrocarbon mass discharge by nearly 80%. Successful anaerobic bioremediation of chlorinated hydrocarbons can be impaired by inadequate concentrations of electron donors, competing electron acceptors, specific inhibitors such as chloroform, and potentially by high contaminant concentrations associated with residual DNAPL. At the study site, the fractured bedrock aquifer was impacted by a mixture of chlorinated solvents and associated daughter products. Concentrations of 1, 1, 2, 2‐tetrachloroethane (1, 1, 2, 2‐TeCA), 1, 1, 2‐trichloroethane (1, 1, 2‐TCA), and 1, 2‐dichloroethane (1, 2‐DCA) were on the order of 100 to 1000 mg/L. Chloroform was present as a co‐contaminant and background sulfate concentrations were approximately 400 mg/L. Following propylene glycol injections, concentrations of organohalide‐respiring bacteria including Dehalococcoides and Dehalogenimonas spp. increased by two to three orders of magnitude across most of the source area. Statistical analysis indicated that reaching volatile fatty acid concentrations greater than 1000 mg/L and depleting sulfate to concentrations less than 50 mg/L were required to achieve a Dehalococcoides concentration greater than the 10 4  cells/mL recommended for generally effective reductive dechlorination. In a limited area, chloroform concentrations greater than 5 mg/L inhibited growth of Dehalococcoides populations despite the availability of electron donor and otherwise appropriate geochemical conditions. After implementing a groundwater recirculation system targeting the inhibited area, chloroform concentrations decreased permitting significant increases in concentrations of Dehalococcoides and vinyl chloride reductase gene copies.